Análise prosódica de preposições monossilábicas - Marcato, Fernanda [UNESP] (2013)
The aim of this work is to describe the prosodic behavior of prepositions “a”, “de”, “por”, “com”, “em”, “do(s)”, “da(s)”, “no(s)”, “na(s)”, “ao(s)”, “à(s)” e “para” from Brazilian Portuguese (PB) variety of São José do Rio Preto (SP), searching for evidence of segmental processes of these prepositions cliticization. For the phonological analysis of data, it has been used Nespor and Vogel’s theory (1986), about the prosodic domains, and it has been considered Bisol’s arguments (2005), on the clitic’s behavior in Brazilian Portuguese Language. As research material, it has been used 32 surveys of spontaneous speech, selected from the census sample database, called IBORUNA - which results from the project Amostra Linguística do Interior Paulista ALIP (FAPESP 03/08058-6), according to the extralinguistic variables controlled in that database, as follows: (i) age, (ii) education level, and (iii) sex/gender. Based on the hearing analysis of the speech surveys, we found several segmental processes and external sandhi that the prepositions are subjected to. In this paper, we describe all these processes and focus on the analysis of joining processes of external vowel sandhi, such as degemination, diphthongization and elision, because they allow investigating the phenomenon of prosodization. From the description of monosyllabic prepositions in the variety to be investigated, we seek to contribute to the characterization and description expansion of spoken Portuguese from Northwest of São Paulo, besides providing a reflection on the prosodic status of these clitic elements in Brazilian Portuguese